On the relationship between hunters and pro-environmental intent. Issue 2 (4th March 2022) - Ghasemi, Benjamin; Kyle, Gerard T.
ABSTRACT: Unprecedented climate change and ecosystem degradation require immediate action at individual and societal levels. It has been suggested that hunting, as a nature-based activity, can contribute to pro-environmental attitudes and behaviors. However, social psychological mechanisms driving hunter engagement in pro-environmental behavior are less understood. We used a sample consisted of hunter and non-hunter students from a large southern U.S. university ( n = 1, 594) to investigate factors associated with intentions to engage in pro-environmental actions. Our results suggested that hunters generally express less pro-environmental intention than do non-hunters. Structural equation modeling showed that hunters' domination value orientation may attenuate their pro-environmental self-identity as the main predictor of pro-environmental intention. Our findings also highlighted the role of connection with nature in fostering pro-environmental behavior. We discuss the theoretical implications of these findings and possible pathways to promote pro-environmental behavior among hunters.